Proposed interview with Lord Halifax : inter-departmental correspondence - Bolton, W. J.
012a-0110-001 W. J. BOLTON International Sir Walter CITRINE 4 April 1938 PROPOSED INTERVIEW WITH LORD HALIFAX With regard to the above, the following replies have been received: Mr. Elvin Agrees Can manage Wednesday. Mr. Bevin Ill Mr. Dukes Agrees Wednesday morning or Friday. Mr. Edwards Agrees Any time. Mr. Holmes Agrees Wednesday or Thursday Mr. Marchbank Agrees Wednesday morning, Thursday morning, all Friday. No replies have yet been received from the provincial members of the Committee. WJB/AC/431. 292/946/12a/110